Development and in vitro evaluation of mefenamic acid orodispersible tablets prepared by direct compression: Mefenamic acid odts: development and in vitro evaluation - Adnan, Muhammad; Raza, Sajid; Saad, Muhammad; Khan, Azhar Abbas; Noman, Muhammad; Aziz Albalawi , Marzough; Alwabsi, Hayam A.; Ali Al-Duais, Mohammed; Sakran, Mohamed; Alharbi , Reem A. K.; Rizk, Nermin I.; Jafri , Ibrahim; et al. (Cellular and Molecular Biology, 2025)
Mefenamic acid functions as a nonsteroidal anti-inflammatory drug (NSAID) of the fenamate class, which treats pain and inflammation by inhibiting cyclooxygenase (COX-1 and COX-2) enzymes to decrease prostaglandin production. Mefenamic acid has strong therapeutic properties that help to treat arthritis and dysmenorrhea. The rapid dissolution of orodispersible tablets (ODTs) makes them an effective treatment option for patients with dysphagia. This study developed and evaluated mefenamic acid ODTs through direct compression while adding super-disintegrants, including croscarmellose sodium, crospovidone, and sodium starch glycolate, to improve drug release and disintegration speed. Pre-formulation analysis through FTIR spectroscopy showed that the drug and excipients maintained compatibility without detectable interactions. Product quality assessment included tests for hardness and weight variation, friability and disintegration time, dissolution studies, and stability testing. The performance of the formulation was evaluated through supplementary tests that measured the moisture uptake, wetting time, and water absorption ratio. The zero-order model provided the most accurate explanation of drug release kinetics among the model-dependent approaches, which included the zero-order, first-order, Higuchi, and Hixson-Crowell models. The combination of 7% croscarmellose sodium in formulation F1 produced the best results by enabling quick dissolution while maintaining the optimal disintegration time and improving drug absorption and patient compliance. Stability tests showed that the formulation structure remained consistent during the entire testing period, thus proving its durability. The direct compression method was effective for manufacturing stable mefenamic acid ODTs according to this research. This research demonstrates how super-disintegrants boost formulation performance, establishing ODTs as a promising drug delivery system for better therapeutic results and patient medication compliance.